Enhancing Daylight Performance and Visual Comfort in Office Buildings with Electrochromic Glazing: A Case Study of Mashhad - H. Kamelnia; A. Ghalehnovi (Iranica Journal of Energy and Environment)
Electrochromic Glazing (EC) has seen a significant surge in adoption today, primarily attributed to its pivotal role in enhancing visual comfort, mitigating excessive heat, regulating cooling and heating requirements, and curbing lighting consumption, especially within office buildings. Moreover, electrochromic glazing effectively contributes to glare control. This research aims to explore the impact of electrochromic glazing, as compared to conventional clear windows, on both the south and north facades, with the overarching goal of enhancing thermal and visual comfort within an office complex located in Mashhad. The research process unfolds in two key steps. Firstly, a comprehensive building simulation was conducted to assess daylight performance and gauge thermal and visual comfort using the GrassHopper plugin. Ubsequently, the Honeybee and Ladybug plugins were harnessed to evaluate the Discomfort Glare Probability (DGP) index and the Useful Daylight Illuminance (UDI) index. The findings of this study underscore the compelling advantages of electrochromic glazing over conventional clear windows as a prime choice to maintain balanced daylight levels throughout the day. In practice, using electrochromic glazing on both north and south facades of a building reduces the annual heating and cooling energy demand by 6.5 and 4.5%, respectively. Additionally, it has a significant impact on reducing intrusive light radiation and intolerable glare levels compared to reference transparent windows, with reductions of 40 and 34.52%, respectively.